Sequential ionic and thermogelation of chitosan spherical hydrogels prepared using superhydrophobic surfaces to immobilize cells and drugs - Lima, A. C. (2014)
Chitosan is soluble in acidic media, which makes it incompatible for the encapsulation of cells and pH-sensitive molecules. In this work, a mild chitosan-based system with two sequential gelation steps is proposed, where the model drug dexamethasone and L929 cells are immobilized inside hydrogel beads. Superhydrophobic surfaces were used to produce the spherical hydrogel particles that provided favorable conditions to encapsulate cells or bioactive agents. First, the chitosan acidic solution was neutralized with β-glycerophosphate at room temperature to pH 6.2. Suspended cells (or dexamethasone) in the formulation were dispensed in controlled volumes onto biomimetic polystyrene superhydrophobic surfaces, to form spherical shapes. The addition of sodium tripolyphosphate on the top of each sphere induced an ionic gelation process of the chitosan through electrostatic interactions. At 37°C, the hydrophobicity of the chitosan-based formulations increased and a second gelation step occurred, which increased the elastic modulus. In addition, the pH-responsive behavior characteristic of chitosan was maintained. The softness and flexibility of the system can potentially be utilized to implant cells and therapeutic molecules using less invasive procedures.